Association between personality traits and psychological burnout among the Coaches of First-Class teams and Sports Unions in Muscat - Al-Ghailani, Salim Mohammed Ali (Journal of Educational and Psychological Sciences, 2024)
This study aimed to explore the relationship between personal traits and psychological burnout among first-team coaches and sports union members in Muscat Governorate, Oman. Through the analysis of data from 110 sports coaches, the results revealed significant differences in the factors causing psychological burnout and personal traits based on demographic variables such as educational level, social status, age, and years of experience. The study showed that psychological burnout among coaches is greatly influenced by their traits, as positive personal traits such as emotional resilience, independence, and creativity can reduce the level of psychological burnout. Additionally, demographic variables play a role in affecting the level of psychological burnout, as coaches with higher educational levels and more experience exhibit greater resilience in the face of work pressures. The study recommends that responsible parties in sports unions and clubs provide necessary support to coaches through training programs that target enhancing positive personal traits and reducing the factors causing psychological burnout. It also advises coaches to develop their personal skills and improve their interaction with professional pressures to maintain their mental and professional health.